Variable vs. invariable elastic response spectrum shapes: impact on the mean annual frequency of exceedance of limit states. (1st July 2020) - Barbagallo, F.; Bosco, M.; Marino, E.M.; Rossi, P.P.
Highlights: The mean annual frequency of exceedance of limit states is evaluated by the MSA. The errors committed using an invariable spectrum shape are determined. The effect of the scattering of spectral accelerations about the mean value is studied. The effect of an approximate hazard relation included in seismic code is investigated. Abstract: In research studies focusing on the evaluation of the fragility function of buildings, numerical analyses are almost always carried out using a single suite of accelerograms, which is scaled in intensity to simulate earthquakes of different magnitude. Therefore, such numerical analyses usually neglect the effects of the variation of important seismological characteristics, e.g. the shape of the pseudo-acceleration response spectrum, on the structural response. To evaluate the impact of the variation of the elastic response spectrum shape with the selected earthquake return period on the mean annual frequency of exceedance of assigned limit state functions, the response of a large set of systems is determined in this paper by two different methods of analysis. In the first method of analysis, a multiple stripe analysis is carried out with accelerograms characterised by median response spectrum shape and ground motion duration variable with the earthquake intensity measure. The information pertaining the probabilistic description of the acceleration spectra has been obtained from the website of the National Institute of Geophysics and Volcanology for the Italian territory, whereas the one regarding the earthquake duration has been derived from semi-empirical relationships reported in the literature. In the second method of analysis, instead, the accelerograms are characterized by median response spectrum shape and ground motion duration invariable with the intensity measure. Finally, to evaluate the influence of the scattering of the spectral responses about their mean value, a third analysis is carried out by means of a set of artificial accelerograms with response spectra that are characterized by virtually zero standard deviation and spectrum shape and ground motion duration invariable with the magnitude of the earthquake. To increase the relevance of the results, the investigated systems include single-degree-of–freedom systems with degrading or non-degrading inelastic response and reinforced concrete and steel multi-degree of freedom systems.